Peristiwa Kudatuli 1996: Gerakan Rakyat dan Pertarungan Politik di Masa Orde Baru - Kurniawan, Fieva Hylmi (Jambura History and Culture Journal, 2025)
The Kudatuli incident (Kudapangan Date Lima) in 1996 was a critical moment in indonesian political history during the New Order era which marked the escalation of conflict between government forces and the pro-democracy movement. This research aims to analyze the people's movements and political dynamics that occurred around this event, as well as their implications for the political stability of society. Using critical historical research methods with a qualitative approach, this research examines historical documents, media reports and in-depth interviews with historical witnesses. The research results show that Kudatuli reflects the accumulation of tension between the political opposition and the government, with the people's movement as an expression of resistance to authoritarianism